The location of InsP3 receptors in Purkinje cells of murine cerebellum does not supports a direct interaction in the transfer of calcium ions between ER and mitochondria - Ramesh Iyer; Clara Franzini-Armstrong (PAGEPress Publications, 2021)
The inositol-3-phosphate receptors (IP3Rs) of cerebellar Purkinje cells are located in abundant, large stacks of endoplasmic reticulum (ER) cisternae. Using thin section electron microscopy, we identify very frequent associations of the ER stacks with mitochondria. The associations have two components: a single, close ER-mitochondria contact on one side to the stack, and multiple layers of ER cisternae decorated by IP3Rs receptors on the side away from the mitochondria. Due to their location in the stacks, IP3Rs are never in contact with the mitochondria, although they are in their vicinity. We conclude that transfer of Ca2+ between ER and mitochondria is not directly mediated by IP3Rs, but is based on mitochondrial Ca2+ uptake from the local cytoplasmic spikes during IP3Rs' activity.